Pengenalan Dan Pembelajaran Ms Office Dan Desain Grafis Sederhana Menggunakan Power Point - Prayoga Pratama; Arkan Abdila Barts; Dava Irba Nusantara; Indah Lasmini; Indra Dwi Aryadi; Lingga Safitri; Pradipa Al-Wafi Putra Prastyo; Rachmat Triyadi; Rico Ronaldo; Tira; Herwis Gultom (Shofanah Media Berkah, 2024)
Pelatihan